Peran Digital Marketing dan Orientasi Pasar terhadap Kinerja Pemasaran dengan Memanfaatkan Keunggulan Bersaing (Industri Gerabah Banyumulek) - Dewi Rispawati; Lale Puspita Kembang; Herawati Khotmi; Yeldi Dwi Genadi; Mahameru Nur Ikhsan Ramadhan; Dian Mila Safitri (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This study aims to examine the influence of digital marketing and market orientation on marketing performance, with competitive advantage as a moderating variable. The research adopts a quantitative approach. The population consists of the pottery industry, with a sample size of 100 respondents. The sampling technique employed was probability sampling. Data were collected through questionnaire distribution. The analysis was conducted using SmartPLS software. Hypothesis testing was based on a P-value threshold of<0.05, indicating hypothesis acceptance. The results reveal that digital marketing has a positive effect on marketing performance, whereas market orientation has a negative effect. Competitive advantage strengthens the relationship between digital marketing and marketing performance, while it weakens the relationship between market orientation and marketing performance. The findings suggest that enhancing digital literacy can reduce the industry’s reliance on traditional marketing, enabling pottery products to compete with modern crafts. Future research is recommended to include additional variables, such as marketing strategy and product quality.